Profil Kondisi Fisik dan Antropometri (Somatothype) Pada Atlet Putri Bulutangkis Usia 10-12 Tahun di Kota Solo Jawa Tengah - Titis Pambudi; Octavian Serka Yudha Pratama; Aditya Trinanda (Journal of Sport Coaching and Physical Education, 2024)
The purpose of this study was to determine the physical condition and somatothype of female badminton athletes aged 10-12 years in Solo City. The population in this study were female athletes aged 10-12 years of achievement who had been on the podium which amounted to 10 athletes. The sampling technique was purposive sampling technique. The sample in this study amounted to 10 athletes. The instruments in this study used tests and measurements referring to physical tests aged 10-12 years (Wiyanto, 2020) and somatothype measurements using the Heath & Carter formula (Carter & Heath, 1990; Penggalih et al., 2018). The results of the physical test of female badminton athletes aged 10-12 years are in the very good category of 2 athletes (20%), good category there are 6 athletes (60%) and moderate category 2 athletes (20%). The results of the somatothype measurement of female badminton athletes aged 10-12 years are in the Mesomorph category of 3 athletes (30%), the Good category is 7 athletes (60%) and the Endomorph category does not exist. In conclusion, female badminton athletes aged 10-12 in the city of Solo have a good level of physical condition (Pratama et al., 2024), and Ectomorph somatothype which tends to have a high posture, little fat in the body and body shape tends to be small.